Abiraterone acetate and prednisone in metastatic castration-resistant prostate cancer: a real-world retrospective study in China - Liu, Min; Yan, Jiaqing; Le, Kaidi; Li, Ying; Xing, Nianzeng; Li, Guohui (Frontiers in Endocrinology, 2023)
Background: This research work was aimed at evaluating the incidence and risk factors of adverse events (AEs) occurring in patients treated with abiraterone acetate (AA) and prednisone (PDN) outside clinical trials. These associations were assessed regarding the survival outcomes. Methods: The study included 191 patients aged ≥18 years of confirmed mCRPC from 2017 to 2022. AEs incidences were descriptively summarized from the whole cohort. Baseline characteristics, safety (treatment-emergent AEs, and severe AEs), and efficacy [progression-free survival (PFS)] were analyzed. Multi-variable Cox proportional hazards models were employed to assess the factors linked with PFS. Results: Overall, the median PFS was 17.16 months (range 0.5 - 57.58). Patient baseline prostate-specific antigen (PSA) ⩾10 ng/mL (p = 0.000), multiple organ metastasis (p = 0.007), hypertension (p = 0.004), and coronary heart disease (p = 0.004) were associated with worse PFS, however, radiotherapy (p = 0.028) was linked to better PFS at univariate analysis in the overall cohort; baseline multiple organ metastasis, hypertension and radiotherapy remained statistically significant in multivariable models (p = 0.007, p= 0.005, p = 0.011 respectively).Incidence of AEs showed increased BIL (55/191 patients, 28.8%) followed by increased ALT-AST (48/191 patients, 25.09%). The most common grade 3 AEs were increased ALT (3/191, 1.57%) followed by elevated BIL, hypercholesterolemia, and hypokalemia. Anemia had shorter PFS. There were no unexpected AEs in any patient. Conclusions: AA is effective and tolerated in asymptomatic or slightly symptomatic mCRPC in “real life” setting. The survival outcomes are influenced by multiple organ metastasis, hypertension, and radiotherapy.